Karakteristik Parkir di Pasar Krian, Kabupaten Sidoarjo - Fauzi, Aditio Achmad; Hartatik, Nurani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Krian market is one of the largest traditional markets in Sidoarjo Regency which has serious problems in providing parking facilities. Limited parking space causes congestion, traffic disruption and inconvenience for visitors and traders. This study aims to analyze parking space requirements and parking characteristics. The research methods used are parking patrol survey and parking space inventory survey. The results show that the limited parking space in Krian market encourages visitors and traders to utilize the road shoulder as a parking area, which in turn worsens traffic conditions. In addition, the high volume of vehicles during peak hours further increases the pressure on the available parking capacity. As a solution, this study recommends the development of additional parking facilities, optimization of existing parking spaces, as well as the implementation of a more effective parking management approach. The implementation of these measures is expected to improve the efficiency of market operations, facilitate vehicle mobility, and create a more organized and comfortable market environment for all parties.